Real-Time IoT-Based Solar Power Monitoring System Using Threshold Decision Algorithm and Mobile Push Notifications - Afif Fathur Rachman; Yasdinul Huda; Ika Parma Dewi; Hadi Kurnia Saputra; Asnal Effendi (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2026)
The establishment of solar power installations as a renewable energy option necessitates dependable monitoring systems to ensure peak performance. Nonetheless, current monitoring solutions typically emphasize only data visualization, lacking intelligent early warning features, which results in slower fault detection and faster battery deterioration. This research tackles this gap by creating a mobile monitoring system based on the Internet of Things (IoT), where both the threshold-based decision algorithm and notification logic are fully integrated into the mobile application, rather than the IoT hardware. The system employs an ESP8266 microcontroller exclusively for gathering data from a PZEM-017 DC sensor, transmitting raw readings to Firebase Realtime Database. A mobile application built on Flutter fetches data, checks it against user-defined thresholds (voltage, current, power), and produces immediate push notifications with anti-spam delays, audio alerts, and optional Telegram sending. Experimental outcomes from 30 measurement locations and 50 anomaly simulations indicate that the system reaches a voltage measurement error of 1.22% and a current error of 9.90% in comparison to a calibrated multimeter. The typical notification delay is 3.4 seconds, significantly less than the 10-second goal. In contrast to edge-based thresholding (on microcontroller), the mobile-centric method enables users to modify thresholds flexibly through the app without the need for hardware reprogramming, offers more extensive notification options (local pop-up, sound, Telegram), and streamlines IoT device upkeep. The specialized mobile interface provides enhanced customization and data logging features in comparison to standard platforms like Blynk or Telegram-based options.